TRAUMATIC BRAIN INJURY (TBI) ET CAUSA HEMATOM SUBDURAL TRAUMATIK DAN FRAKTUR OS OCCIPITAL: SEBUAH LAPORAN KASUS - DARUMURTI, RISSITO CENTRICIA; RACHMAWATI, FITRI FAIZA (JURNAL ILMIAH SIMANTEK, 2024)
Head injury or traumatic brain injury (TBI) is defined as a mechanical trauma to the head directly or indirectly that causes impaired neurological function, namely physical, cognitive, psychosocial functioning, both temporarily and permanently. The national prevalence of head trauma according to Riskesdas in 2013 increased 0.7% to 8.2% where men are twice as likely to experience head injuries than women. The diagnosis of head injury is established based on anamnesis in the form of post-traumatic disorders of the head followed by the presence or absence of disturbances of consciousness or lucid intervals, otorrhea or rhinorrhea, and post-traumatic amnesia. Neurological clinical assessment is necessary to assess whether there are signs of focal deficits. Supporting examinations in the form of imaging with a plain photo of the head in the AP/lateral/tangential position or with a CT scan of the head. 61-year-old man came with a history of fainting for five minutes which was preceded by a headache and profuse vomiting after being hit by a tree branch on the back of his head. On physical examination he was conscious of compos mentis and found a 4cm hematom in right occipital region. On ECG found sinus bradycardia. General status and other neurological status within normal limits. Radiological results showed an extracranial hematoma in the occipitoparietal region, a subdural hematoma in the right occipital lobe and a fracture of the right occipital bone. Patient received nasal cannula oxygenation, asering and mannitol infusion, tranexamic acid, citicholin and piracetam injection. The condition of the head injury in this case was a severe head injury as indicated by the presence of a subdural hematoma and fracture in the right occipital region even though the patient's consciousness from GCS was normal. The patient's condition improved after administration of osmotic diuretics, antifibrinolytics and neuroprotectant agents.